Art heterotopias against hegemonic discourses: Dancing the Cyprus conflict - Christofidou, Andria; Milioni, Dimitra L. (My University, 2023)
We provide an analysis of dance as a practice and an ‘Other’ space; a counter-hegemonic ‘space’, which is affected by the existing social ordering, while simultaneously resisting it. We employ Foucault’s concept of ‘heterotopia’ to analyse dance’s potential to disrupt and deconstruct hegemonic discourses of the past in a conflict-ridden environment such as Cyprus. We analyse three dance works by choreographers who are living and working in Cyprus, and while we focus on the interrelated dimensions of time, space and the (choreographic) subject, we demonstrate how dance may (1) provide a space to problematize the past and recraft the present, (2) enable the re-signification of places of conflict into places of communication and peace and (3) invite artists to reflect on their subjectivities and transform into agents of peace.
Keywords: Conflict; Cyprus; Dance; Heterotopia; Peace; Resistance